WHY MUST I CRY? JUSTIFICATION, SACRIFICE, LONELINESS, MADNESS AND LAUGHTER IN POSTAPARTHEID JUDICIAL DECISION-MAKING (The Pretoria Student Law Review, 2021)
Peter Tosh’s plaintive – ‘Why must I cry?’ – is normally interpreted to be about a lost lover. It probably is. But I am going to propose a different reading. I am going to pretend that Peter Tosh is a conscientious South African judge with postmodernist and critical legal tendencies. This judge is concerned with the massive responsibility she feels as a judge in post-apartheid South Africa. Not only must she walk the lonely, lonely, lonely road of ordinary judicial office, she must bear the big heavy load of the specific social, economic and political circumstances that place added pressure on her to transform, both society and herself. At the same time, she is confronted with critical theories that seek to impose an even greater burden on her in the form of unanswerable calls to justice and unfulfillable duties to the other. These theories are, on the whole, framed in a way that is both critical of judges and largely pessimistic about the possibility of success. Many of the theories specifically require the judge to mourn her inability to do the impossible. For many reasons then, our hypothetical judge asks: ‘Why must I cry?’ My answer in brief is: She need not cry. She must not cry. I will argue that the best means to address the various responsibilities imposed on judicial officers is through laughter, not tears. I begin by detailing the ‘culture of justification’ that dominates both judicial and academic thinking (I will look specifically at Mureinik, Klare and Botha) and examine exactly what burdens this philosophy imposes on judges. Next I acknowledge that the burdens of justification, onerous as they may be, are not enough. I adopt Van der Walt’s ideal of ‘law as sacrifice’ to argue that all judges have the additional duty to acknowledge the sacrifices that are an inescapable part their profession. I conclude by looking at humour and the law. Humour in judicial decisions has played an often unnoticed role (more in America than South Africa!)
Keywords: Peter Tosh; ‘Why must I cry?’; judge in post-apartheid South Africa; transformation; justice; unfulfillable duties; judicial officers; ‘culture of justification’; ‘law as sacrifice’